Canada's Arctic policy. Striking a balance between national interests and circumpolar cooperation - Steinveg, Beate (UiT Norges arktiske universitet, 2014)
The Arctic is undergoing rapid changes, both environmentally and politically, and the Arctic states as well as non-Arctic actors are working to establish a presence, secure national interests and natural resources in the High North. Canada is an interesting player in this unpredictable region, with the potential to become an Arctic great power. Canada is the world’s second largest country, over 40% of its landmass is located in the north, it has an extensive Arctic coastline and considerable prospects for northern energy and natural resource development. At the same time, Canada’s northern territories – the Yukon, the Northwest Territories and Nunavut – are severely underdeveloped. Both the federal and the territorial governments face enormous challenges in terms of social and economic development, infrastructure improvements, providing education and job opportunities, improving housing conditions and the health of Aboriginal peoples and northerners in the territories. These challenges notwithstanding, it is crucial for the federal government to facilitate the continued habitation of the Canadian Arctic to assert and maintain its sovereignty claims to the region, which is becoming increasingly vital as international interests in the circumpolar north grows. To deepen the understanding of how Canada works to position itself in the High North, this thesis sets out to answer the problem statement: what are the main priorities for Canada in its Arctic region, and how does Canada pursue its Arctic policy on the domestic and international level? The thesis examines how Canada works domestically and maneuvers on the international arena to respond to challenges in the region while safeguarding domestic interests and protecting its Arctic sovereignty. It focuses on policy issues pursued unilaterally, through bilateral relations with the other Arctic states and through transnational cooperation in multilateral forums, primarily the Arctic Council. It presents Canada’s actions, intentions and motives behind these actions, ...